Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals (Platygyra daedalea) of the Arabian/Persian Gulf. Issue 24 (17th December 2018) - Kirk, Nathan L.; Howells, Emily J.; Abrego, David; Burt, John A.; Meyer, Eli
Abstract: Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal tolerance, estimate potential future adaptive responses and understand the functional basis for these corals' unusual heat tolerance, we conducted controlled crosses in the Gulf coral Platygyra daedalea . Heat tolerance is highly heritable in this population ( h 2 = 0.487–0.748), suggesting substantial potential for adaptive responses to selection for elevated temperatures. To identify genetic markers associated with this variation, we conducted genomewide SNP genotyping in parental corals and tested for relationships between paternal genotype and offspring thermal tolerance. Resulting multilocus SNP genotypes explained a large fraction of variation in thermal tolerance in these crosses (69%). To investigate the functional basis of these differences in thermal tolerance, we profiled transcriptional responses in tolerant and susceptible families, revealing substantial sire effects on transcriptional responses to thermal stress. We also studied sequence variation in these expressed sequences, identifying alleles and functional groups of differentially expressed genes associated with thermal tolerance. Our findings demonstrate that corals in this population harbour extensive genetic variation in thermal tolerance, and heat‐tolerant phenotypes differ in both gene sequences and transcriptional stress responses from their susceptible counterparts.